European Social Model and East Asian Economic Model - Different Approach to Productivity and Competition in Economy - Prokurat, Sergiusz (Europejski Model Społeczny i Wschodnioazjatycki Model Ekonomiczny - różne podejścia do zjawisk produktywności i konkurencji, 2010)
The economic success of the East Asian countries has inspired many scholars and policy makers to study the background of their rapid growth. Since there are many versions of capitalism, there is a debate over which model is the best answer for people needs. This debate is still open. In the article the author describes and compares the basis of both the European Social Model (ESM) and East Asian Economic Model (EAEM). In the summary he states that the manner of thinking of economy is the factor differentiating European and Asian societies, but also that the current system and the perception of the idea of competitiveness affects the country's development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 35-47
Keywords: competitiveness; rivalry; European model; Asian model